Learning and assistive technologies for college transition. - Asselin, Susan B. (Journal of Vocational Rehabilitation, 2014)
Today's college environment requires knowledge and skill with a variety of learning technologies. Transition planning for students with disabilities addresses academic preparation with limited attention paid to teaching students to use emerging technologies or assistive technologies for learning. Transition assessment that includes learning and assistive technologies provides students with a better understanding of the impact of their disability in the college environment and how to advocate for appropriate accommodations based on this data. While assistive technologies are considered academic accommodations, emerging technologies which are universally designed for a broader range of users offer the opportunity to increase accessibility of information technology. The availability of web based information and built in features opens doors for students to strengthen individual cognitive and functional skills necessary for college success. Access to these technologies affords individuals with disabilities the flexible, yet individualized means to communicate and engage in increasingly digital learning environments.